A Study on Lao Phuan Vernacular House in Ngan Area, Khoun District, Xieng Khuang Province: https://doi.org/10.69692/SUJMRD09081 - Daravong, Sinthavone; Pathoumxay, Sommany; Waenvongthong, Phongern (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The study on vernacular houses of the Lao Phuan ethnic group aims to determine the area that still retains most of its original form, as defined by the fieldwork of Ngan area in Khoun District, Xieng Khouang Province as a case study. The selected area is the only one that still has a large number of traditional houses left behind. Through the study of relevant documents, physical surveys with maps and observations, random measurements of house components, and in-depth interviews with village chiefs, the elderly, and residents in the village: These Lao Phuan vernacular houses are designed and built to meet the needs of their occupations and to suit the nature or environment of the area in which they reside. Including their traditions, culture, and way of living. This can be seen from using materials that are easy to find, durable in use, and abundant locally, such as using Longleng wood as a roofing material. In addition, to being a natural sense, it is also an extra sun and rain-resistant material, making it usable for decades. At the same time, the style of the house has long eaves with small windows, which is due to the fact that the area is located in an area with high rainfall. In addition, the stilt house form will be used as a storage area for daily production equipment, firewood, fishing tools, and weaving equipment, as well as for survival and safety conditions. The use of space inside the house, in addition to allocating the area to serve a basic living, also allocated a large hall area to accommodate guests or relatives who visit regularly. Especially when there are traditional events held in the village or gift ceremonies inside the house. Another important point is that the area has to adapt to the dry season (winter). Therefore, two fireplaces have been set up; the first is in the cooking area. The second point is in the living area to use the fireplace to keep warm, the process of building a house still follows the strict traditions and beliefs that have been practiced for a long time.